2007
DOI: 10.1002/jbm.b.30828
|View full text |Cite
|
Sign up to set email alerts
|

Development of an engineering autologous palatal mucosa‐like tissue for potential clinical applications

Abstract: The goal of this study was to optimize key processes in recreating functional and viable palatal mucosa-like tissue that would be easy to handle and would promote wound healing. Normal human gingival fibroblasts and epithelial cells and a clinically useful biomaterial, CollaTape, were used. Structural and ultrastructural analyses showed that the gingival fibroblasts and epithelial cells adhered to the biomaterial and proliferated. Following a 6-day culture, using 10(5) fibroblasts and 10(6) epithelial cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 30 publications
0
14
0
3
Order By: Relevance
“…The CollaTape is a biocompatible three-dimentional porous soft collagen sponge easy to handle with good mechanical properties. It is already approved for human use basically in dental surgery, but also as a scaffold for in vitro [27] and in vivo tissue engineering [28]. Because of the coherent sponge structure and composition, its use in this study will be of great interest in engineering a chitosan-collagen composite scaffold.…”
Section: Methodsmentioning
confidence: 99%
“…The CollaTape is a biocompatible three-dimentional porous soft collagen sponge easy to handle with good mechanical properties. It is already approved for human use basically in dental surgery, but also as a scaffold for in vitro [27] and in vivo tissue engineering [28]. Because of the coherent sponge structure and composition, its use in this study will be of great interest in engineering a chitosan-collagen composite scaffold.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that wound contraction and scar formation on the palate after palatoplasty caused the maxillary growth retardation 3. Presently, extensive literatures suggested that by using tissue engineered palatal mucosa substitutes to cover the denuded bone wounds could reduce the extent of wound contraction and scar formation 4–6…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture into different matrices, including allogeneic skin substitutes, has been studied and has shown promising results in the regeneration of soft tissues 5‐14 . The acellular dermal matrix (ADM) † in particular is probably the most used and studied of the allogeneic subcutaneous substitutes.…”
mentioning
confidence: 99%